Struvite Precipitation and Phosphorous Removal from Urine Synthetic Solution: Reaction Kinetic Study - Marwa Saied Shalaby; Shadia El-Rafie (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Phosphorus, like oil, is a non-renewable resource that must be harvested from finite resources in the earth’s crust. An essential element for life, phosphorus is becoming increasingly scarce, contaminated, and difficult to extract. Struvite or magnesium ammonium phosphate (MgNH4PO4.6H2O) is a white, crystalline phosphate mineral that can be used as a bio-available fertilizer. The main objective of this research is to indicate the most important operating parameters affecting struvite precipitation by means of chemical reaction kinetics. The present study explores struvite precipitation by chemical method under different starting molar ratios, pH and SSR. It is shown that an increase of starting Mg: PO4: NH4 with respect to magnesium (1.6:1:1) strongly influences the growth rate of struvite and so the efficiency of the phosphate removal. This was attributed to the effect of magnesium on the struvite solubility product and on the reached supersaturation Super Saturation Ratio at optimum starting molar ratio and pH. It was also shown, by using chemical precipitation method that the determined Super Saturation Ratio (SSR) values of struvite, at 8, 8.5, 9, 9.5 and 10 are 1.314, 4.29, 8.89, 9.87 and 14.89 respectively are close to those presented in the literature for different origins of wastewater streams. The results show that SSR , pH, and starting molar ratio strongly influences the kinetics of precipitation and so phosphorous removal to reach 93% removal percent , 5.95 mg/lit as a minimum PO4 remained in solution, and 7.9 gm precipitated struvite from feed synthetic solution of 750 ml . The product was subjected to chemical analysis by means of EDIX-FTIR, SEM and XRD showing conformity with published literature. First-order kinetics was found to be sufficient to describe the rate data. The rates increased with increasing pH and so SSR and the apparent rate constants for the reaction were determined.  © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)